ADDITIONAL NOTE ON CULLENIA CEYLANICA K. Schum. (Bombac) - A. J. G. H. KOSTERMANS (Research Center for Biology, 1958)
Cullenia excelsa Wight in Pearson & Brown, Commerc. Timb. India 1: 141, t. 51 1932; Foxworthy in Philipp. J. Sci. Bot. 4: 500. 1909; Trotter, Common Comm. Timb. India 65. 1901. Foxworthy in Philip. J. Sci. Bot. 4: 500. 1909. Fruit collected in January 1958 from the tree cultivated in the Bogor. Botanical Garden (no. XVI H. 13) enables me to correct and emendate the description published in